2017
DOI: 10.1007/s10549-017-4623-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of palbociclib plus fulvestrant after everolimus in hormone receptor-positive metastatic breast cancer

Abstract: In this heavily pretreated population including everolimus, fulvestrant plus palbociclib provides an mPFS of 5.8 months with the same magnitude of benefit for fulvestrant-pretreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
4
31
0
Order By: Relevance
“…These data are consistent with previous reports of in vitro studies that show CDK4/6 inhibitors can reverse acquired resistance to inhibitors of PI3K [36]. Data from two clinical studies with small numbers of patients indicate that palbociclib-based therapies have limited efficacy after progression on the mTORC1 inhibitor everolimus (RAD001) [37,38]. However, the efficacy of CDK4/6 inhibition post-progression on PI3K inhibitor-based therapies is yet to be investigated.…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with previous reports of in vitro studies that show CDK4/6 inhibitors can reverse acquired resistance to inhibitors of PI3K [36]. Data from two clinical studies with small numbers of patients indicate that palbociclib-based therapies have limited efficacy after progression on the mTORC1 inhibitor everolimus (RAD001) [37,38]. However, the efficacy of CDK4/6 inhibition post-progression on PI3K inhibitor-based therapies is yet to be investigated.…”
Section: Discussionsupporting
confidence: 90%
“…With a longer follow-up, subsequent large US and international studies have shown similar PFS data and have suggested an OS benefit [13,14]. Other, more limited studies, were in line with those results [26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 58%
“…A prospective nonrandomized single-arm study of the efficacy of palbociclib plus fulvestrant after everolimus in France showed a median PFS after palbociclib combination to be 5.8 months (95% CI, 3.9-7.3). 12 A total of 26.7% had partial response, while 45% had stable disease as best response. No CBR was reported.…”
Section: Discussionmentioning
confidence: 96%